2009
DOI: 10.1097/jto.0b013e3181ba31e0
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Pemetrexed Plus Cisplatin as First-Line Therapy for Advanced Nonsquamous Non-small Cell Lung Cancer

Abstract: Compared with commonly used and reimbursed regimens for first-line chemotherapy in advanced NSCLC, Cis/Pem may be considered cost-effective, particularly in patients with nonsquamous cell histology. This analysis emphasizes the importance of histology in identifying the appropriate patient for Cis/Pem first-line chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 21 publications
0
48
0
1
Order By: Relevance
“…Only one of these cost-effectiveness analysis (CEAs) included QALYs as an outcome of interest, but all three CEAs and our study used survival as a common outcome measure to determine ICERs. Klein et al reported an ICER of $337,179 per life-year gained (LY) for carboplatin, paclitaxel, and bevacizumab (as used in the ECOG 4599 trial) compared with cisplatin and pemetrexed, suggesting that the addition of bevacizumab is not cost-effective when compared with more recent and expensive regimens [10]. Grusenmeyer et al [12] performed a CEA similar to our study, based on the ECOG 4599 trial, and reported an ICER of $345,762/LY, which is similar to the ICER we report ($309,000/LY).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Only one of these cost-effectiveness analysis (CEAs) included QALYs as an outcome of interest, but all three CEAs and our study used survival as a common outcome measure to determine ICERs. Klein et al reported an ICER of $337,179 per life-year gained (LY) for carboplatin, paclitaxel, and bevacizumab (as used in the ECOG 4599 trial) compared with cisplatin and pemetrexed, suggesting that the addition of bevacizumab is not cost-effective when compared with more recent and expensive regimens [10]. Grusenmeyer et al [12] performed a CEA similar to our study, based on the ECOG 4599 trial, and reported an ICER of $345,762/LY, which is similar to the ICER we report ($309,000/LY).…”
Section: Discussionmentioning
confidence: 98%
“…Three studies have addressed the cost-effectiveness of the addition of bevacizumab to chemotherapy in NSCLC [10 -12]. Two of these studies used indirect treatment comparison methods to determine the cost-effectiveness of cisplatin and pemetrexed relative to other regimens including carboplatin, paclitaxel, and bevacizumab [10] and to determine the cost-effectiveness of cisplatin, gemcitabine, and bevacizumab versus cisplatin and pemetrexed [11]. The third study reported a cost-effectiveness ratio of US$345,762 per year of life gained for the addition of bevacizumab to carboplatin and paclitaxel [12].…”
Section: Introductionmentioning
confidence: 99%
“…Klein et al [17] ont réalisé en 2009 une analyse coût-efficacité du pemetrexed en première ligne dans l'essai CBPNAPC non épider-moïde. Il s'agissait de l'analyse coût-efficacité de l'article comparant l'utilisation de cisplatine et de pemetrexed en première ligne dans les CBP NAPC non épidermoïdes avec d'autres types de chimiothérapie Tableau 2.…”
Section: Dossierunclassified
“…Several pharmacoeconomic analyses of pemetrexed for firstline and second-line treatment have been reported [15][16][17]. However, economic assessments for maintenance/consolidation therapy are limited, with only a single analysis having been performed in a US population [18].…”
Section: Introductionmentioning
confidence: 99%